Elevated plasma EDA fibronectin in primary myelofibrosis is determined by high allele burden of JAK2V617F mutation and strongly predicts splenomegaly progression - Malara, Alessandro; Gruppi, Cristian; Massa, Margherita; Tira, Maria Enrica; Rosti, Vittorio; Balduini, Alessandra; Barosi, Giovanni (Frontiers in Oncology, 2022)
In primary myelofibrosis (PMF), extra-domain A fibronectin (EDA-FN), the result of alternative splicing of FN gene, sustains megakaryocyte proliferation and confers a pro-inflammatory phenotype to bone marrow (BM) cell niches. In this work we measured the plasma levels of EDA-FN in 122 well characterized patients with PMF. A homozygous JAK2V617F genotype was the major determinant of elevated plasma EDA-FN. Elevated EDA-FN levels were associated with anemia, increased levels of high-sensitivity C-reactive protein, BM fibrosis and splanchnic vein thrombosis at diagnosis. While, no correlation was observed with CD34+ hematopoietic stem cell mobilization, elevated plasma levels of EDA-FN at diagnosis predicted large splenomegaly (more than 10 cm from the left costal margin) outcome. Thus, EDA-FN expression in PMF may represent the first marker of disease progression, and a novel target to treat splenomegaly in PMF.